2015
DOI: 10.1002/jwmg.884
|View full text |Cite
|
Sign up to set email alerts
|

Prescribed fire and timber harvest effects on terrestrial salamander abundance, detectability, and microhabitat use

Abstract: Prescribed fire and timber harvest are anthropogenic disturbances that modify resource availability and ecosystem structure, and can affect wildlife both directly and indirectly. Terrestrial salamanders are effective indicators of forest health due to their high abundance and sensitivity to microclimatic conditions. Given their ecological importance, it is critical to understand how forest salamanders respond to management‐related disturbances. We predicted that timber harvest and prescribed fire would decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 65 publications
(98 reference statements)
4
25
0
Order By: Relevance
“…This could be due to higher activity levels associated with decreased litter depth or cover and associated changes in microclimate, changes in prey availability, or expanded foraging areas (Homyack et al 2011). In contrast, other studies reported short‐term decreased surface activity and abundance, and increased use of cover objects after 1 (O'Donnell et al , 2016) or 2 (Ford et al ) low‐intensity dormant‐season prescribed burns in upland hardwood forest, based on diurnal plot searches or coverboard methods.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…This could be due to higher activity levels associated with decreased litter depth or cover and associated changes in microclimate, changes in prey availability, or expanded foraging areas (Homyack et al 2011). In contrast, other studies reported short‐term decreased surface activity and abundance, and increased use of cover objects after 1 (O'Donnell et al , 2016) or 2 (Ford et al ) low‐intensity dormant‐season prescribed burns in upland hardwood forest, based on diurnal plot searches or coverboard methods.…”
Section: Discussionmentioning
confidence: 90%
“…Subsequent results following a second burn in burn‐only and mechanical + burn (2006–2007) showed no difference in plethodontid salamanders in 2006 but fewer in mechanical + burn than burn‐only or control in 2007 (Matthews et al ). Several other studies showed that 1 or 2 low‐intensity, dormant‐season burns do not adversely affect terrestrial salamanders (Ford et al , O'Donnell et al , Raybuck et al , Seiboldt , Greenberg et al ). Importantly, the long‐term results from this study indicate that, despite some variability among some treatments within individual years (Matthews et al ), terrestrial salamander abundance did not decline overall, even after 4 repeated burns in burn‐only and mechanical + burn, and further canopy cover reduction in mechanical + burn.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations